2018
DOI: 10.1177/1468796818788596
|View full text |Cite
|
Sign up to set email alerts
|

“We don’t do that in Germany!” A critical race theory examination of Turkish heritage young adults’ school experiences

Abstract: Turkish heritage students are underrepresented at university-track secondary schools in Germany, yet the institutional discrimination contributing to this ongoing disparity often remains unquestioned, situated within inequitable norms of belonging. Drawing on critical race theory and a risk and resilience framework, the current study investigated the interplay between institutional and interpersonal discrimination in relation to exclusionary norms enacted in university-track schools. Using thematic analysis, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 93 publications
(99 reference statements)
2
33
0
Order By: Relevance
“…This result underlines the need for teachers to not only identify ethnic discrimination, but to also address it. To do so, culturally responsive training in anti‐bullying programmes and also “teacher reflexivity regarding” (their own) bias and discussion about ethnic discrimination and its implications are needed (Moffitt et al, ). As stated at the outset of this article, schools are one of the first and most influential service systems that refugee students encounter in the host county.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This result underlines the need for teachers to not only identify ethnic discrimination, but to also address it. To do so, culturally responsive training in anti‐bullying programmes and also “teacher reflexivity regarding” (their own) bias and discussion about ethnic discrimination and its implications are needed (Moffitt et al, ). As stated at the outset of this article, schools are one of the first and most influential service systems that refugee students encounter in the host county.…”
Section: Resultsmentioning
confidence: 99%
“…While Othering and ethnic discrimination often occur amongst peers, teachers can also be perpetrators of this. In their explorative qualitative study of German young adults with Turkish backgrounds, for example, Moffit, Juang, and Syed () recently showed that these students experienced ethnic discrimination from their teachers during their Gymnasium (university‐track school) years. Their findings reveal that particular teachers perpetuate discriminatory norms (e.g., no intervention for peer ethnic discrimination), hold low expectations for the students in question and, in this context, promote ethno‐cultural norms of what it means to be “German.” This ethnic discrimination has many consequences on the individual student, lowering self‐esteem, leading to feelings of loneliness and depression and affecting academic performance (Fazel et al, ).…”
mentioning
confidence: 99%
“…By implication, Austrian citizens from immigrant-background require visas to visit their country of origin or that of their parents. Similar to Anglophone Western nations (Burt et al 2012;Ghafournia and Easteal 2018;Graber 2019;Hipp and Kubrin 2017;Pepper 2017;Polanco 2015), and non-Anglophone Western nations such as Italy (Colombo et al 2009;Policek et al 2019), Germany (Kranz 2017;Moffitt et al 2018), 'immigrant-citizens' have inherited the negativisation bestowed historically upon those who are culturally 'Other' in Austria (Zaslove 2004;Refaie 2001;Horvath 2014;Cochrane and Nevitte 2014). As a consequence, there is widespread vilification of immigrants in the media and in political discourse that is well documented (Hipfl and Gronold 2011;Messinger 2013;Rheindorf and Ruth 2019).…”
Section: State Of the Art In Literature: Austriamentioning
confidence: 99%
“…Bicultural individuals may be disadvantaged with regard to school engagement and school performance when facing discrimination (Baysu, Phalet, & Brown, 2011). The more boys feel discriminated against, especially by teachers (Moffitt et al, 2018), the more they may perceive that heritage and mainstream cultures are incompatible, and the more they may endorse either culture, but not both (Lepshokova et al, 2017). As a result, highly stigmatized individuals of immigrant background are at risk to turn away from the mainstream society in several life domains, and may attribute a lack of personal success and societal engagement to cultural barriers in society (Azghari, van de Vijver, & Hooghiemstra, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The authors argued that perceiving high amounts of ethnic-racial socialization at home may increase adolescents' awareness of cultural issues outside of home, including a higher perception of ethnic discrimination. In addition, ethnic discrimination by mainstream teachers is part of ethnicity-related school experiences for many students with immigrant background in Germany (Moffitt, Juang, & Syed, 2018).…”
Section: Acculturation Expectations By Parents and In School And Ethmentioning
confidence: 99%